Threats to western private forests strategic initiative: a collaborative process addressing threats to the health and sustainability of private forests in the western U.S. - Coelho, Dana, author (Colorado State University. Libraries, 2009)
The business of managing private forestland is changing. Globalization of markets, broad economic forces, government regulations and ecological stresses (such as fire and climate change) have completely altered the operating environment for forest landowners seeking to manage their land. Large multinational timber companies are able to achieve the financial efficiencies to deal with global-scale market forces, but smaller operators have few tools to help them adjust to the increasing complexity. A new business model within a new policy framework is needed to address the needs of private forest landowners, as well as those of the local, state and federal agencies and environmental organizations who offer financial and technical assistance. In the interest of helping members of the forestry community "retool" to allow them to continue managing their forests without relying solely on traditional timber harvest models, the Western Forestry Leadership Coalition (WFLC) convened a series of stakeholder workshops to identify the threats to private forests and forestry. In short, why and how are the ecological and social benefits, and the economic viability of western private forests at risk? Five workshops were held in different regions around the West, which brought together representatives from state forestry and wildlife agencies, Tribes, local government, U.S. Forest Service, Bureau of Land Management, industry, academia, conservation organizations and, most importantly, private forest landowners. Additional listening sessions were held with foresters from the U.S. affiliated Pacific Islands. The workshops generated a large body of ideas with regard to both threats and creative remedies. Workshop participants agreed on the need to emphasize the scarcity and value of private forest lands. Private forests often provide ecological strongholds, significant islands of biodiversity and wildlife corridors. Their value as recreational areas or access points to public recreation sites is huge. Yet, private forests make up a small percentage of the overall western landscape and can be overlooked despite their importance. From here, a drafting group will build upon the workshop results to create a report published by the WFLC and endorsed by workshop participants. The report, along with policy briefs developed by participants and partners, will be distributed to key policy makers at all levels of government to facilitate appropriate recommendations to address barriers to maintaining private working forests. Congressional testimony, memos to agency leadership and resolutions made at the state and local levels will carry the messages towards implementation on the ground. Change may be inevitable for many working forests, but their continued management offers the flexibility to adapt to change in ways that unmanaged and converted lands clearly do not. In the end, this flexibility will help private forest landowners continue to provide the many ecological, economic and social benefits expected by their local and global neighbors – including a buffer against potential climate change. Just as working lands offer resilience through flexibility, the forestry community has to be flexible in adapting to a new business model that will make healthy forest management possible and financially sustainable.
Threats to western private forests
Poster presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. The presenter is Program Manager at Western Forestry Leadership Coalition (WFLC).
Keywords: WFLC; ecological threats; western U.S.; private forests; collaborative conservation; Western Forestry Leadership Coalition